2014
DOI: 10.1073/pnas.1412009111
|View full text |Cite
|
Sign up to set email alerts
|

Deorphanization of the human leukocyte tyrosine kinase (LTK) receptor by a signaling screen of the extracellular proteome

Abstract: There are many transmembrane receptor-like proteins whose ligands have not been identified. A strategy for finding ligands when little is known about their tissue source is to screen each extracellular protein individually expressed in an array format by using a sensitive functional readout. Taking this approach, we have screened a large collection (3,191 proteins) of extracellular proteins for their ability to activate signaling of an orphan receptor, leukocyte tyrosine kinase (LTK). Only two related secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 22 publications
1
57
2
Order By: Relevance
“…AUG-α stimulates robust kinase activity of both ALK and LTK at picomolar concentrations on cells and binds the ECD of ALK and LTK with dissociation constants in the low nanomolar range. We also found that AUG-β, which was previously shown to be a ligand for LTK (25), could stimulate only weak autophosphorylation of ALK at high subnanomolar concentrations, but could strongly stimulate LTK at picomolar concentrations (a schematic model of hierarchy and specificity of ligand-receptor interactions is depicted in Fig. 4F).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…AUG-α stimulates robust kinase activity of both ALK and LTK at picomolar concentrations on cells and binds the ECD of ALK and LTK with dissociation constants in the low nanomolar range. We also found that AUG-β, which was previously shown to be a ligand for LTK (25), could stimulate only weak autophosphorylation of ALK at high subnanomolar concentrations, but could strongly stimulate LTK at picomolar concentrations (a schematic model of hierarchy and specificity of ligand-receptor interactions is depicted in Fig. 4F).…”
Section: Discussionsupporting
confidence: 67%
“…We have recently demonstrated that ALK expressed in the NB1 cell line can be activated by heparin (but not by pleiotrophin or midkine), suggesting a proteoglycan may regulate ALK activity and function through binding to its heparin-binding NTR (15). Two small proteins, designated FAM150A and FAM150B, were recently identified in a screening assay for secreted proteins that bind to the recombinant extracellular domain of LTK (25). It was also demonstrated that FAM150A binding results in stimulation of LTK activation, indicating that FAM150A can function as a stimulatory ligand of LTK.…”
mentioning
confidence: 99%
“…Thus, LTK remained an enigmatic receptor tyrosine kinase. The ER localization of LTK was recently questioned by reports showing that it responds to extracellular ligands . We showed that endogenous as well as overexpressed LTK localize to the ER and we did not detect any evidence that LTK ever leaves the ER .…”
Section: Signaling From the Ercontrasting
confidence: 75%
“…It was proposed that GDF11 promotes skeletal muscle regeneration by restoring genomic integrity of old skeletal muscle satellite cells (SCs) and thereby promoting their outgrowth in response to injury (Sinha et al ., 2014). To identify factors that may regulate the growth with aging, we screened a comprehensive expression library of extracellular proteins (Zhang et al ., 2014) on aged skeletal muscle SCs (additional screen details to be published elsewhere). Given the reported activity of GDF11, we expected to identify it in our screen.…”
mentioning
confidence: 99%